2017
DOI: 10.3390/ma10080858
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Bio-Degradation Rate of the Hydrothermal-Synthesizing Coated Mg Alloy via Pre-Solid-Solution Treatment

Abstract: In this study, we report an effective approach, pre-solid solution (SS) treatment, to reduce the in-vitro bio-degradation rate of the hydrothermal-synthesizing coated Mg–2Zn–Mn–Ca–Ce alloy in Hanks’ solution. Pre-SS treatment alters the microstructure of alloys, which benefits the corrosion resistances of the substrate itself and the formed coating as well. The micro-galvanic corrosion between the secondary phase (cathode) and the α-Mg phase (anode) is relieved due to the reduction of the secondary phase. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Among them, the hydrothermal (HT) method [8] is quite attractive due to the simple one-step process, environmental friendliness, and easy design of the reaction conditions. The corrosion properties of magnesium alloys can be enhanced by the formation of oxide and/or hydroxide films via HT treatment [9]. MgO and Mg(OH) 2 constitute good protective films on account of the nontoxic and biocompatible properties [10].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the hydrothermal (HT) method [8] is quite attractive due to the simple one-step process, environmental friendliness, and easy design of the reaction conditions. The corrosion properties of magnesium alloys can be enhanced by the formation of oxide and/or hydroxide films via HT treatment [9]. MgO and Mg(OH) 2 constitute good protective films on account of the nontoxic and biocompatible properties [10].…”
Section: Introductionmentioning
confidence: 99%
“…As such, it is of great significance to reduce the secondary phase of the Mg alloy substrate (the contribution of H380), in order to improve the coating integrity and its protection against corrosion. Song et al reported similar outcomes, where pre-solid-solution treatment could effectively improve the coating integrity of a Mg-2Zn-Mn-Ca-Ce alloy [28]. Considering that the performance of the heat-treated samples was superior, the following animal experiments only used the ARRm-H380 and ARRm-H380-F24 h alloys to examine the practicability.…”
Section: Figure 10mentioning
confidence: 93%
“…Meanwhile, the SS alloy kept a continuous slow increase in OCP value during the whole tested immersion period, indicating the superior stability of the surface film. EIS is widely used in the investigation of electrochemical corrosion behavior of metallic materials, which has a great advantage in continuously monitoring the evolution of corrosion characteristic [58][59][60]. Figure 6a and b are the EIS Nyquist plots of the tested alloys obtained from the different immersion periods in the 0.1 mol/L NaCl solution.…”
Section: Corrosion Behavior and Corrosion-resistance Enhancement Mechmentioning
confidence: 99%